Peningkatan Kualitas Kesehatan Melalui Program Rumah Sehat di Pulau Ngenang Kota Batam - Oktarizal, Hengky; Sari, Novela (ASOSIASI IDEBAHASA KEPRI, 2024)
Pulau Ngenang, Batam City, faces significant challenges related to access to clean water and adequate sanitation, which negatively impact public health. The Healthy House Program is designed to address these issues through infrastructure improvements, health education, and increased public awareness. This study aims to evaluate the effectiveness of the Healthy House Program in improving the health quality of the Pulau Ngenang community. The methods used include qualitative and quantitative approaches, with initial and final health surveys, field observations, and in-depth interviews with household representatives. The results show significant improvements in access to clean water, sanitation facilities, and a reduction in the incidence of diseases such as diarrhea and skin diseases. Health education has increased the community's knowledge and awareness of healthy living practices. Field observations confirm that renovated houses have better ventilation, increased use of clean water, and improved sanitation systems. Interviews with household representatives reveal that the community has experienced direct benefits from the program, including improved quality of life and productivity. The conclusion is that the Healthy House Program has successfully improved the health and well-being of the Pulau Ngenang community. For the program's sustainability, continued technical and financial support, ongoing health education, additional program development, and collaboration with various stakeholders are recommended. With joint commitment, this program can continue to develop and provide long-term benefits for public health.